Genetic Complexity of Hormone Sensitive Cancers - Batra, Jyotsna (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this Special Issue, authors from nine countries on five continents provide overviews on and insights into current research topics related to the ‘Genetic Complexity of Hormone-Sensitive Cancers’. The chapters cover topics on completely novel technologies and instruments revolutionizing our view of biological entities, and also, novel extensions and revisions of existing and well-established technologies such as genetic probes and bar-coding techniques, which add a new dimension to microscopy, as they allow us to visualize DNA sequences and mRNA in situ. With this Special Issue, the editors wanted to create a forum for the international biomedical research community to compile their data on the genetic complexity of cancer in a unique resource. While this collection of articles cannot certainly claim completeness in any way, it represents an attractive collection of the different aspects of hormone-dependent cancers and will hopefully encourage further targeted research.